Experimental characterization and modelling of drying of pear slices - Doymaz, Ibrahim; Ismail, Osman (KOREAN SOCIETY FOOD SCIENCE & TECHNOLOGY-KOSFOST, 2012)
The effect of temperature on the drying kinetics of pear slices was investigated. The drying process was carried out at temperatures of 55, 65, and 75A degrees C. Drying time decreased considerably with increased air temperature. Seven mathematical models available in the literature were tested with the drying patterns. The Wang and Singh, and Midilli et al. models were given the best results in describing drying of pear slices. Effective moisture diffusivity increased with increasing air temperature, and varied from 0.85 to 2.18x10(-10) m(2)/s over the temperature range investigated, with activation energy equal to 44.78 kJ/mol.
Keywords: activation energy; effective moisture diffusivity; convection drying; mathematical modelling; pear; MOISTURE DIFFUSIVITY; KINETICS; DEHYDRATION; MICROWAVE; PLUM; Food Science & Technology